Diskriminasi Terhadap Perempuan: Analisis Budaya Sebambangan Perspektif Feminisme - Ririn Setiawati; Zulkiply Lessy (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
Culture is basically an important thing in society, but there are some cultures that have a more negative impact. The culture that appears in general still clearly shows its alignment with men, one of these cultures is the Sebambangan culture. Sebambangan culture is more inclined to men so that it puts women in a disadvantaged position. The purpose of this study is to examine Sebambangan culture from the point of view of Feminism. The research method in this paper is a descriptive-qualitative method with a Feminist approach. The population in this study is the entire Lampung tribal community by taking samples using a purposive sampling technique. The results of this study indicate that based on feminism studies, the sebambangan culture makes women marginalized and subordinated in society. Based on this, the existence of a culture that has more negative impacts can certainly be repaired or abandoned.